IDENTIFIKASI KESALAHAN TERHADAP HASIL TERJEMAHAN MESIN BAHASA INGGRIS KE BAHASA JAWA: KAJIAN SEMANTIK - Meilawati, Avi; Nursanti, Emi (Diksi, 2018)
Abstract (Title: Identification of Errors on English Engineering Translation Results to Java Language: Semantic Study). This study uses linguistic principles to study the results of English to Javanese translations using an online translation engine. In particular, this study aims to identify translation errors and study them from a semantic perspective. Data is obtained by entering ten thousand samples of English sentences into the Google Translator translation engine which are then analyzed qualitatively. Analysis is focused on the level of words and phrases. The results of the study show four main problems in the semantic domain, namely the absence of lexicons, the inaccuracy of lexicons, word ambiguity, and idiom phrases. Suggestions were given to improve the quality of Javanese language SMT from a linguistic perspective, related to quantity, coverage, and quality of corporate data.Keywords: semantics, machine translator, Javanese, English, linguistics